Presentation of Robot-Intended Handover Position Using Vibrotactile Interface During Robot-to-Human Handover Task - Bin Mohammed Zaffir, Muhammad Akmal; Wada, Takahiro (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Advancements in robot autonomy and safety have enabled close interactions, such as object handovers, with humans. During robot-to-human handovers in assembly tasks, the robot considers the state of the human to determine its optimal handover position and timing. However, humans may struggle to focus on their primary tasks because of the need to track the robot's movement. This study aims to develop a vibrotactile interface that helps humans maintain focus on their primary tasks during object reception. The interface conveys the robot-intended handover position on the human forearm by displaying the angular direction and distance relative to the human hand via vibrotactile cues. The experimental results demonstrated that the interface allowed participants to receive objects with faster reactions and completion times, with reduced head rotation towards the robot. Participants also subjectively perceived improved performance and reduced mental workload compared with the condition without the interface.CCS CONCEPTS* Human-centered computing → Human computer interaction (HCI); Collaborative interaction; Haptic devices; User interface programming.